PENGARUH MODEL PEMBELAJARAN PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMAN 2 SUTERA - Yusi Mardila (Jurnal Edukasi dan Penelitian Matematika, 2021)
Problem solving ability is onemof the desires that have to be achieved in learning mathematics. However, based..onmthe results of observationsmmade at SMAN 2 Sutera,  it changed into determined that scholars' mathematical problem..solvingmabilities were stillnlow. One.ofmthe efforts that..can be done to overcome these problems is by applying the..model Problem Based Learning (PBL)nin the mathematics learning process. The purpose of this studynwas to determine how the impact of the application of the model Problem Based Learning on the problem solving abilities of students in class XI SMAN 2 Sutera. The type of research used is pre-experimental research with a research design using a onenshot case.study. The subject of this research is class XI SMAN 2 Sutera. The researchninstrument is.in thenform of a mathematicalnproblem solvingnability test in the form of anquestion essay. The data obtained were analyzed based on the number of students, average scores, and the percentage of students' scores per indicator. Based totally at the consequences of the analysis of research records, it suggests that the development of mathematical problem solving abilities of class XI students of SMAN 2 Sutera whose leaming by applying the nmodel Problem Based Learning (PBL) is quite good and has increased in several indicators, namely understanding problems, planning solutions, and solving problems.Problem solving ability is one of the goals that must be achieved in learning nmathematics. However, basednon the results of observations made at SmAN 2 Sutera, it was found thatnstudents' mathematical problemnsolving abilities were still low. One of the efforts that can be done to overcome these problems is by applying the model ProblemnBased Learning (PBL)nin the mathematics leaming process. The purpose of this study was to determine how the impact of the application of themodel Problem Based Leaming on the problem solving abilities of students in class XI SMAN 2 Sutera. The type of research used is pre-experimental research with a research design using a one shot case study. The subject of this research is class XI SMAN 2 Sutera. The research instrument is in the form of a mathematical problem solving ability test in the form of anquestion essay. The data obtained were analyzed based on the number of students, average scores, and the percentage of students' scores per indicator. Based onnthe resultsnof the analysis..of..researchndata,,,itnshows..that the development of mathematicalnproblemnsolving abilities of class XI students of SMAN 2 Sutera whose leaming bypapplying the model ProblemmBased Learning (PBL) is quite good and has increased in several indicators, namelyuunderstanding problems, planningnsolutions, and solvinggproblems. Keywords — Mathematical Problem Solving Skill, Problem Based Learning model